Dynamic resource allocation schemes during handoff for mobile multimedia wireless networks. - Ramanathan, P. (IEEE Journal on selected areas in communications)
User mobility management is one of the important components of mobile multimedia systems. In a cell-based network, a mobile should be able to seamlessly obtain transmission resources after handoff to a new base station. This is essential for both service continuity and quality of service assurance. In this paper, we present strategies for accommodating continuous service to mobile users through estimating resource requirements of potential handoff connections. A diverse mix of heterogeneous traffic with diverse resource requirements is considered. The investigate static and dynamic resource allocation schemes. The dynamic scheme probabilistically estimates the potential number of connections that will be handed off from neighboring cells, for each class of traffic. The performance of these strategies in terms of connection blocking probabilities for handoff and local new connection requests are evaluated. The performance is also compared to a scheme previously proposed by Yu and Leung (see IEEE J. Select. Areas Commun., vol.15, p.1208-25, 1997). The results indicate that using dynamic estimation and allocation, we can significantly reduce the dropping probability for handoff connections